Fostering Digitalization of Construction Projects through Integration: A Conceptual Project Governance Model - Liu, Zhixue; Ding, Ronggui; Gong, Zheng; Ejohwomu, Obuks (Buildings (Basel), 2023)
The construction industry has fared poorly in the process of digital transformation, while the main challenge is the digitalization of construction projects. Changes in project management approaches are urgently required in construction organizations to better align digital technology and organizational conditions. However, little literature has explored the pivotal role of the project management approach from an organizational perspective. To fill this gap, this research investigates ways of using a project governance model for integration to promote the digitalization of construction projects through a case study. The three integration dimensions, namely stakeholder integration, lifecycle integration, and project management knowledge integration, are identified, and governance elements under each dimension are displayed—and further stratified—based on the three levels of the governance model, including institutional level, organizational level, and behavioral level. The logical relationship between elements and their roles in project digitization is finally summarized. The developed conceptual model will provide an approach for construction enterprises to promote project digitalization.